Pyriproxyfen promotes lipid accumulation in 3T3‐L1 adipocytes by enhancement of TR4 activity. Issue 3 (23rd May 2014) - Choi, Hojung; Kim, Eungseok
Abstract Insect hormones and their synthetic analogs have been suggested to modulate gene expression in mammals. Thus, we investigated to determine the role of pyriproxyfen, a juvenile hormone (JH) analog, in the transcriptional activity of TR4, which functions as a key modulator of energy homeostasis. Here, we demonstrate that 100 μM pyriproxyfen enhances TR4 transcriptional activity with increase of expression of TR4 target genes such as FATP1 and PEPCK in 3T3‐L1 adipocytes. Furthermore, pyriproxyfen treatment resulted in increase of lipid accumulation during adipocyte differentiation of 3T3‐L1 cells. In reporter gene assays, pyriproxyfen promotes TR4 transactivation of the reporter genes linked to different target gene promoters. Knockdown of TR4 in 3T3‐L1 cells abolished promoting effect of 100 μM pyriproxyfen on lipid accumulation and expression of lipogenic genes, suggesting that pyriproxyfen may regulate adipogenesis of 3T3‐L1 cells via modulation of TR4 transcriptional activity. Together, our results suggest that pyriproxyfen, a JH analog, may modulate lipid homeostasis in adipocytes via regulation of TR4 activity.